2012
DOI: 10.1371/journal.pone.0029976
|View full text |Cite
|
Sign up to set email alerts
|

Wnt4 Participates in the Formation of Vertebrate Neuromuscular Junction

Abstract: Neuromuscular junction (NMJ) formation requires the highly coordinated communication of several reciprocal signaling processes between motoneurons and their muscle targets. Identification of the early, spatially restricted cues in target recognition at the NMJ is still poorly documented, especially in mammals. Wnt signaling is one of the key pathways regulating synaptic connectivity. Here, we report that Wnt4 contributes to the formation of vertebrate NMJ in vivo. Results from a microarray screen and quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 51 publications
2
92
1
Order By: Relevance
“…In zebrafish, both Wnt4a and Wnt11r initiate muscle prepatterning, probably by stimulating PCP-dependent MuSK endocytosis in muscle cells (Gordon et al, 2012;Jing et al, 2009). In mice, although recent data have challenged the role of Wnts at the NMJ (Remédio et al, 2016; discussed below), we have demonstrated that Wnt4 contributes to muscle prepatterning (Strochlic et al, 2012). Wnt signaling is also required for later steps of vertebrate NMJ differentiation.…”
Section: Introductionmentioning
confidence: 46%
See 3 more Smart Citations
“…In zebrafish, both Wnt4a and Wnt11r initiate muscle prepatterning, probably by stimulating PCP-dependent MuSK endocytosis in muscle cells (Gordon et al, 2012;Jing et al, 2009). In mice, although recent data have challenged the role of Wnts at the NMJ (Remédio et al, 2016; discussed below), we have demonstrated that Wnt4 contributes to muscle prepatterning (Strochlic et al, 2012). Wnt signaling is also required for later steps of vertebrate NMJ differentiation.…”
Section: Introductionmentioning
confidence: 46%
“…Growing evidence in several vertebrate species, using both in vitro and in vivo models, suggests that Wnt morphogens act as regulators of NMJ initiation and/or formation (Gordon et al, 2012;Henriquez et al, 2008;Jing et al, 2009;Messéant et al, 2015;Packard et al, 2002;Strochlic et al, 2012;Zhang et al, 2012). Yet, Wnt function and the molecular mechanisms through which Wnts collaborate at the mammalian NMJ remain elusive and controversial.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mammalian muscle cells, five Wnts (Wnt9a, Wnt9b, Wnt10b, Wnt11 and Wnt16), presumably by direct binding to MuSK, are able to stimulate AChR clustering, in a manner dependent on LRP4 . Recently, WNT4 has been implicated in muscle pre-patterning and to stimulate AChR clustering via activation of MuSK (Strochlic et al, 2012). In addition, agrin-induced AChR clustering was enhanced by WNT3, but reduced by WNT3a (Henriquez et al, 2008;.…”
Section: Wnt Signaling or Cadherin Signaling In Nmj Formationmentioning
confidence: 99%